Playing by the Rules: Due Process and Errors of State Procedural Law - Martha I. Morgan (Washington University Law Quarterly, 1985)
A striking example of the Court's failure to elevate violations of established state procedural safeguards to a violation of due process is found in Barclay v. Florida. In Barclay, the Court upheld a death sentence admittedly imposed in violation of state law. The first section of this Article examines the foundations and support for the respective approaches of Justices Rehnquist, Marshall, and Blackmun in the Barclay case. The second part of this Article argues that due process requires compliance with established procedural safeguards when a government seeks to deprive a person of life, liberty, or property. This Article proposes a "fair play" approach to defining due process that builds upon Justice Blackmun's "rule of law" approach in Barclay. This approach recognizes that procedural "unfairness" may occur in two ways. First, the procedural rules themselves may be unfair. Second, the government's disregard of established procedural safeguards also is unfair. This second variety of unfairness exists regardless of whether the Constitution would otherwise require that the particular safeguard be provided. The fair play interpretation, therefore, posits that both unfair rules and failure to play by established rules violate due process. The final section of this Article discusses some effects the fair play approach would have upon traditional notions of federalism.
Keywords: Due process of law